Sugar responsiveness could determine foraging patterns in yellowjackets - Masciocchi, Maité (2023)
Sympatric-related species often exhibit resource partitioning. This can occur through different mechanisms, such as behavioral, morphological, and sensory variations, leading to qualitative, temporal, or spatial differences in resource exploitation, such as consuming different types of food. Sensory-based niche partitioning could be the underlying mechanism through which closely related species effectively reduce niche overlap. Here we ask whether variations in sensory responses to carbohydrates could reflect differences in the foraging patterns of two Vespula species present in Patagonia. For this, we established (i) the response thresholds toward carbohydrate solutions of foraging V. germanica and V. vulgaris in the laboratory, (ii) the sugar concentration of foraged carbohydrates in the field, and (iii) possible effects of incoming sugar concentration and performance at individual and colony levels. Results indicate a higher sucrose response threshold in V. germanica than V. vulgaris. Field results indicate that higher carbohydrate concentrations foraged by V. germanica, with 57% of V. germanica foragers returning with concentrations above 50% w/w, while only 23% of V. vulgaris foragers did so. These differences in sucrose sensitivity and foraging patterns positively correlate with colony size, irrespective of the species. Our results suggest that competition could be reduced in these closely related invasive social wasp species through sensory differences in their sugar perception levels, which would lead to them foraging different carbohydrate sources. This study suggests that sensory niche partitioning could promote species coexistence in these social wasps.